Moving Forward: Gradual Return of Gastroenterology Practice during the COVID-19 Pandemic - Francisco, Carlos Paolo (Dig Dis, 2020)
BACKGROUND: The COVID-19 pandemic has caused disruption of routine gastroenterology practice, which has resulted in the suspension of elective endoscopic procedures and outpatient consults. For the past months, the strategy was to mitigate infection risk for the healthcare team while still providing essential service to patients. Prolonged suspension of the outpatient clinics and endoscopy practice, however, is deemed unsustainable and could even be detrimental. It can compromise patient care and result in poor outcomes; hence, a well-crafted plan is needed for the gradual resumption of clinic operations and endoscopic procedures. SUMMARY: As the world begins to transition to the “new normal,” there are new health and safety issues to consider. Adaptive measures like telemedicine and electronic health records should be utilized to facilitate patient care while minimizing exposure. Careful patient screening, adequate supply of personal protective equipment, effective infection-control policies, as well as appropriate administrative modifications are needed for a safe return of gastroenterology practice. KEY MESSAGES: Ensuring the safety of patients, caregivers, and healthcare workers should remain as top priority. To help ease the transition as we move forward from this pandemic, we present a review of recommendations to guide gastroenterologists and endoscopy unit administrators in the gradual return to gastroenterology practice.